Domestic abuse : contemporary perspectives and innovative practices - Brooks-Hay, Oona; Burman, Michèle; McFeely, Clare (Policy and practice in health and social care, 2018)
Domestic abuse is a global health and social problem. This edited volume considers Scottish responses in a wide comparative context.